Improving Rice Farmers’ Livelihoods through Participatory Crop Support and Seed Distribution in Collaboration with UPTD in Cihanyawar Village - Arifin, Irlansyah; Tri, Rindi; Aulia, Nova; Rahmawati, Siti; Ananda, Ristiany; Yulinda, Elma; Nuraeni, Wini; Saputri, Meisa; Rizqi, Muhamad; Suci, Kuntum; Rachmadio, R. Edy (PT Agung Media Publisher, 2025)
This community service initiative was designed to improve rice farmers’ livelihoods through a participatory support program involving seed distribution and collaborative agricultural assistance with the Regional Technical Implementation Unit (UPTD) in Cihanyawar Village. The program integrated the strengths of academic institutions and local agricultural agencies to deliver targeted support aimed at increasing productivity and income. Using a participatory action research approach, the six-month program engaged 50 farmers through four key phases: preparation, implementation, monitoring, and evaluation. Three superior rice varieties IR64, Ciherang, and Inpari-32, were distributed, accompanied by intensive training in modern cultivation techniques, integrated pest management, and sustainable farming practices. The initiative led to a 61.9% increase in rice yield, from 4.2 to 6.8 tons per hectare, with Inpari-32 performing the highest at 7.2 tons per hectare. Economically, farmers’ gross income rose by 55.3%, from IDR 8.5 million to IDR 13.2 million per hectare per season, with a benefit-cost ratio of 6.27. Knowledge transfer was also effective, as farmers’ mastery of modern practices improved from 23% to 87%. Notably, 78% of participating farmers expressed commitment to continue the improved practices. The success of this collaborative model underscores the potential of participatory and institutional synergy in promoting sustainable improvements in farmers’ livelihoods. This model can serve as a practical reference for future agricultural development programs in similar rural contexts.